Application of phosphate fertilization on banana hybrid ‘FHIA 18’and its impact on production performance - Bolfarini, Ana Carolina Batista [UNESP]; Putti, Fernando Ferrari [UNESP]; Souza, Jackson Mirellys Azevedo [UNESP]; de Souza Silva, Marcelo [UNESP]; Ferreira, Rafael Bibiano [UNESP]; Leonel, Magali [UNESP]; Tecchio, Marco Antonio [UNESP]; Leonel, Sarita [UNESP] (Southern Cross Publishing, 2020)
FHIA 18 is a hybrid banana that could replace cultivar Prata, which is highly affected by Black Sigatoka and Panama disease. Still, there is a paucity of literature on FHIA 18 nutrient requirements, especially phosphorus. Nevertheless, we aimed to estimate the best phosphorus levels and its effect on the productive characteristics of FHIA 18 during three crop cycles in the city of São Manuel, state of São Paulo. Triple superphosphate has been given at recommended rates of 0, 20, 30, 40, 50 and 60 kg P2O5 ha-1 year-1 for three crop cycles that occurred in January 2014 (first cycle), August 2014 (second cycle) and June 2015 (third cycle). Results indicated that maximum fruit number per bunch was achieved at 30 and 26 kg P2O5 ha-1, corresponding to second and third cycle, respectively. Moreover, there was an increase in bunch mass, fruit mass, number of hands per bunch, mass and length of the fruit in the second hand, when P2O5 reached its maximum values from 20 to 34 kg P2O5 ha-1 year-1, but fruits diameter decreased. Results also showed that FHIA 18 required lower level of P2O5 to achieve maximum yield than the recommended doses for other banana cultivars in the state of São Paulo. Therefore, this current study recommends a rate of 22 kg P2O5 ha-1 year-1 for FHIA 18 to reach its maximum production.
Keywords: Genetic improvement; Musa spp; Nutrition; P2O5; Production; P_Phosphorus